History of the Development of the Thai Constitution - Norkaew, Yutthasart (Journal of Public Administration Chiang Rai Rajabhat University, 2023)
This article Aiming at reviewing the development of the Thai Constitution Since the influence of constitutional ideas came to the land of Siam during the reign of King Mongkut (King Rama IV) onwards, which is considered an international political trend that has been widely discussed and criticized around the world. During that time until the creation of the first constitution in the period after "Siamese Revolution 1932" and appears to have developed continuously. Throughout the period between 1932 and 2017, Thailand had a total of 20 constitutions enacted through a dynamic social, economic, and political context. Whether it is the feudal warlord era half-democracy era People's Democratic Era and the democratic era with different colors of shirts, this makes it known that the Thai Constitution has its roots in a revolution, a coup, and drafting by the people. Drafting by the legislature includes drafting by officials or the military through legislative bodies, in order to focus on the succession of power through constitutional mechanisms. Therefore, revisiting the history of the Thai constitution allows us to thoroughly reconsider the social, economic, and political contexts of each era. It also leads to a concrete analysis, prediction, and prediction of the nature of the Thai Constitution in the future.